Acute bacterial septic vasculopathy. (11th December 2012) - Delgado‐Jiménez, Yolanda; Fraga, Javier; Requena, Celia; Requena, Luis; Aragües, Maximiliano; Fernandez Herrera, Jesus; Diez, Amaro Garcia
Abstract Objectives The frequency and clinicopathologic characteristics of cutaneous lesions in sepsis are not well known. This study aimed to analyze cutaneous lesions in bacterial septic vasculopathy. Methods The study population comprised 32 patients with bacterial sepsis, cutaneous lesions, and skin biopsy‐proven septic vasculopathy. The clinical and histologic characteristics of the lesions were analyzed. Findings in non‐immunosuppressed patients (NISPs) and immunosuppressed patients (ISPs) were compared. Results Nine of 32 patients were immunosuppressed. The foci of sepsis were variable; in 17 patients, the focus was not identified. Although Neisseria meningitidis was the most common causal agent, several microorganisms were identified. Cutaneous manifestations were an early event in 90.6% of patients. The most common skin signs were purpuric lesions and petechiae. Overall mortality was 28.1%; 65.5% of patients survived without sequelae. Skin biopsies showed thrombi in 100% of cases. Other common findings were inflammatory infiltrate, blood extravasation, and epidermal involvement. Bacteria within the vascular wall were seen in 21.9% of cases and fibrinoid necrosis in 25%. A comparison of ISPs with NISPs disclosed that meningococcemia was more common in the latter group, and the presence of pustules was more common in the former. Histopathology testing revealed that fibrinoid necrosis and bacterial invasion of the vessel wall were more common in ISPs than in NISPs. Conclusions Several microorganisms can cause septic vasculopathy. Clinical presentation is variable and does not depend on the microorganism or the pathogenic mechanism. Histopathologically, septic vasculopathy is a thrombo‐occlusive vasculopathy with variable morphology. Cutaneous lesions are an early event and allow for rapid diagnosis.